Impact of COVID-19 pandemic (wave 2) and associated lockdown on wound care and the resultant increase in the number of amputations - G., Lokesh M.; S., Chandrashekar; Talwar, Vini (International Journal of Research in Medical Sciences, 2021)
Background: The COVID-19 pandemic has had an unparalleled impact on the socio-economic and healthcare structure of the entire world, including India. The risk of major amputations has increased during the COVID-19 lockdown. Aim of the study was to conduct a single-centered study on the prevalence of major amputations during the pre-pandemic and pandemic period to evaluate the indirect effect of the COVID-19 lockdown on people with lower limb cellulites and wounds. This study also emphasizes on the importance of easy and routine access to foot-care specialist. Methods: The data of patients attending the outpatient and emergency room of general surgery in K. R. Hospital with complaints of cellulites/wounds/ulcers during the months of March to July was evaluated. The number of amputations done during same time period was analyzed. Results: The patients attending outpatient department (OPD) during the lockdown had a fall, while cases and amputations immediately after lockdown had increased. Conclusions: The findings of the present study, reiterate the role of preventive actions in wound care and stress on the importance awareness of complications if such wounds are ignored.